The Qur'an and Inter-Religious Relation Models in Contemporary World - Kurdi Fadal (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2020)
This article examines interreligious relations during the Qur’anic revelation and its contextualization in the contemporary world. This library research, focusing on ‘Ali Jum’ah’s thought, utilizes a qualitative with a historical approach. The results of this research show that the Qur'an was revealed in four models of Muslim and non-Muslim relations: the Meccan period model; the Habasyah phase, the first migration of some Muslims and as a minority under non-Muslims authority; and two Medina periods (the Early and the Latter) when Muslims become a majority who lived together peacefully with other religious communities under Muslim authority. Ali Jum'ah uses nasā’ as a theory to contextualize the four models of interfaith relations. According to him, each of these models can be applied and developed in contemporary Muslims, especially in the Indonesian context, based on the principles of the Qur'an.